Mosque Loudspeakers and Social Harmony: Community Contestation in the Environment Grand Mosque of Surakarta Palace - Zaenal Muttaqin; Supriyanto; Muhammad Agus Wahyudi (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
In the context of a pluralistic urban society, religious practices in public spaces often give rise to social dynamics between religious expression and shared comfort. This study examines public perceptions of the use of loudspeakers at the Great Mosque of the Surakarta Palace (Masjid Agung Kraton Surakarta) as part of Islamic preaching practices within a pluralistic public sphere. Employing a qualitative approach, data were collected through semi-structured interviews with individuals residing in the vicinity of the mosque. Informants were selected using purposive sampling, and the data were analyzed using thematic analysis. The findings reveal a diversity of perceptions influenced by respondents’ socio-religious backgrounds. The religious-conservative group views the loudspeaker as an indispensable tool for Islamic proselytization (da'wah). The moderate-pragmatic group adopts an adaptive and tolerant stance, provided that the practice does not disrupt socio-economic activities. Meanwhile, the critical-reflective group advocates for regulated use of loudspeakers to preserve collective comfort. Within the framework of Talcott Parsons’ structural functionalism, these religious practices reflect the four functional imperatives of the AGIL scheme: adaptation, goal attainment, integration, and latency. Nevertheless, potential dysfunctions may arise when symbolic religious expressions are not aligned with the heterogeneous social context. These findings underscore the necessity of fostering social dialogue and adopting moderate policies to maintain intercommunal harmony in urban-plural societies.